An In Vitro Evaluation of Leakage of Two Etch and Rinse and Two Self-Etch Adhesives after Thermocycling - Sabine Geerts; Amandine Bolette; Laurence Seidel; Audrey Guéders (International Journal of Dentistry)
Our experiment evaluated the microleakage in resin composite restorations bonded to dental tissues with different adhesive systems. 40 class V cavities were prepared on the facial and lingual surfaces of each tooth with coronal margins in enamel and apical margins in cementum (root dentin). The teeth were restored with Z100 resin composite bonded with different adhesive systems: Scotchbond Multipurpose (SBMP), a 3-step Etch and Rinse adhesive, Adper Scotchbond 1 XT (SB1), a 2-step Etch and Rinse adhesive, AdheSE One (ADSE-1), a 1-step Self-Etch adhesive, and AdheSE (ADSE), a 2-step Self-Etch adhesive. Teeth were thermocycled and immersed in 50% silver nitrate solution. When both interfaces were considered, SBMP has exhibited significantly less microleakage than other adhesive systems (resp., for SB1, ADSE-1 and ADSE, 𝑃=0.0007, 𝑃<0.0001 and 𝑃<0.0001). When enamel and dentin interfaces were evaluated separately, (1) for the Self-Etch adhesives, microleakage was found greater at enamel than at dentin interfaces (for ADSE, 𝑃=0.024 and for ADSE-1, 𝑃<0.0001); (2) for the Etch and Rinse adhesive systems, there was no significant difference between enamel and dentin interfaces; (3) SBMP was found significantly better than other adhesives both at enamel and dentin interfaces. In our experiment Etch and Rinse adhesives remain better than Self-Etch adhesives at enamel interface. In addition, there was no statistical difference between 1-step (ADSE-1) and 2-step (ADSE) Self-Etch adhesives.